Periphytic diatoms as bioindicators in a tropical stream: from urban to rural environments - Moresco, Carina; Gubiani, Éder André; Rodrigues, Liliana (Acta Scientiarum. Biological Sciences, 2015)
Urbanization and agriculture alter expressively the physical and chemical variables of lotic habitats, especially streams, causing negative effects to the biota of these environments. This study aimed to (i) evaluate the spatial and seasonal variations in the structure of periphytic diatom assemblage in a stream under urban influence in its headwaters, and rural influence, in the rest of its course, and (ii) select diatom species as bioindicators of urban and rural stretches. Three sampling sites were set along the stream according to its longitudinal gradient. The structure of the periphytic diatom assemblage presented differences in spatial scale, differing substantially between the urban and rural habitats. There was a higher influence of nutrients (orthophosphate (PO4) and total nitrogen (TN)) on the distribution of the assemblage. Therefore, the use of the assemblage of periphytic diatoms as environmental bioindicator indicated spatial differences along the riverine areas, from the agriculture environment to the urbanized environment.